First report of the interaction between the toad Melanophryniscus nigricans and the leech Helobdella cordobensis in the Tandilia Mountains - Tejedor, Facundo (2025)
Melanophryniscus nigricans is an endangered endemic anuran species restricted to the Tandilia Mountains in Argentina. We report for the first time the interaction between this toad species and the leech Helobdella cordobensis. We observed the interaction in a temporary pond at the “Sierra del Tigre” Natural Reserve during a breeding event of M. nigricans on February 7th, 2024. A leech was found attached to the belly of a toad and removed manually with no evidence of injury in the amphibian, suggesting a case of phoresis instead of parasitism. This report is also the first documented phoretic interaction between H. cordobensis and anurans from Argentina.